Successful treatment of reactive hemophagocytic syndrome with cyclosporin A and intravenous immunoglobulin - Erduran, Erol; Gedik, Yusuf; Şen, Yaşar; Yıldıran, Alişan (The Turkish Journal of Pediatrics, 2000)
Infection-associated hemophagocytic syndrome (IAHS) is a form of the reactive hemophagocytic syndrome. IAHS is associated with viral, bacterial, fungal, mycobacterial, rickettsial and protozoal infections and with various malignant neoplasms. A more accurate designation for this acquired form of the syndrome is reactive hemophagocytic syndrome (HS). Reactive HS is characterized by malaise, fever, hepatosplenomegaly, lymphadenopathy, cytopenia, hypertriglyceridemia, hypofibrinogenemia and hemophagocytosis. Cyclosporin A, VP-16, high-dose steroids, and intravenous immunoglobulin (IVIG) have been used in the treatment of IAHS. Here, a 10-year-old girl with reactive HS due to possible viral infection was treated successfully with cyclosporin A and IVIG. Fever disappeared on the third day, complete blood count reached normal levels on the sixth day and hepatosplenomegaly disappeared on the ninth day after treatment.We believe cyclosporin A and IVIG may be used in the treatment of reactive HS, at least in selected patients. Further studies are required to confirm its role as first-line therapy for children with IAHS.
Keywords: reactive hemophagocytic syndrome; intravenous immunoglobulin; cyclosporin A